Murabbi: who are we? - Md. Noon, Hazizan (2015)
This presentation defines the concept of Murabbi in the context of International Islamic University Malaysia (IIUM). It elaborates the roles that the Murabbis should play in the University bydiscussing the aims of IIUM Murabbi and some examples of the Murabbis' tasks.